Parents in the School System in Europe - Nina V. Shabrova (National Research Mordova State University, 2022)
Introduction. To determine the prospects for the development of the social community of parents as a subject of civil society in Russia it is necessary to analyze foreign practices of social and civil activities of parents. In this sense, the activities of European parents are of interest, reflecting the experience of countries with a developed civil society (France, Germany, Sweden). The aim of the article is to analyze the institutional opportunities and practices of European parentsʼ participation in the system of school education. Materials and Methods. The methodological framework for the study of parentsʼ involvement in childrenʼs education was the concept of D. Epstein. To achieve this goal, the content of normative documents regulating the participation of European parents in the education of their school children was studied; a secondary analysis of statistical information and scientific publications was carried out. Results. The study showed that despite the common European space, parents of the analyzed countries have different institutional opportunities to participate in the education of their children. Two basic principles of state policy in relation to the parent community, which affect the peculiarities of their participation in school education, are highlighted. The first principle is the restriction of the freedom of individual choice of parents in the field of school education to ensure equal access to public school education. The second is the priority of childrenʼs rights over the rights of parents. The interaction of the school with parents is focused on the education of politically correct parents who fulfill the requirements of the school. It is noted that the Russian parent community can more actively use at least two European practices for the implementation and protection of parental and children rights and interests in the field of school education: collective forms of protection of rights and interests; consolidation with the local community for the implementation of parental and children needs and interests. Discussion and Conclusion. The obtained results contribute to the development of the sociological concept of the parent community as a subject of civil society. The materials of the article will be useful to scientists analyzing the problems of the development of Russian civil society; representatives of educational management engaged in the development of programs for the harmonization of relations between parents and schools; civil activists.